Circ_0058063 contributes to oral squamous cell carcinoma development by sponging miR‐145‐5p and upregulating SERPINE1. (4th August 2022) - Yu, Jie; Lou, Ying; Hou, Ming; Ma, Xin; Wang, Lu
Abstract: Background: We aimed to demonstrate the effects circ_0058063 exerted on oral squamous cell carcinoma (OSCC) and its downstream mechanism associated with miR‐145‐5p and SERPINE1. Methods: The relevant contents of miR‐145‐5p, circ 0058063, and SERPINE1 mRNAs in OSCC were evaluated using quantitative reverse transcription polymerase chain reaction. Functional experiments including CCK‐8, Transwell, Western blot, and in vivo experiment were implemented to investigate the biological impacts on OSCC cells. Using dual‐luciferase reporter, RIP, and RNA pull‐down assays, the direct binding relationship between miR‐145‐5p, circ 0058063, and SERPINE1, SMAD3, CYR61, and IGF1R mRNAs was verified. Results: In OSCC, Circ 0058063 was significantly overexpressed. Knockdown of circ_0058063 suppressed OSCC cell migration and proliferation, but enhanced cell apoptosis. Functionally and mechanistically, circ_0058063 could specifically bind with miR‐145‐5p and thus upregulated expression of downstream target SERPINE1, which together contributed to the progression of OSCC. Conclusion: Circ_0058063 could promote the malignant behavior of OSCC by upregulating SERPINE1 through sponging miR‐145‐5p.